2014
DOI: 10.1007/s11250-014-0545-1
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and non-carcass component yields of crossbred Boer and Brazilian semiarid indigenous goats subjected to different feeding levels

Abstract: The effect of different feeding levels (ad libitum, 25 and 50 % restriction) and genotypes (½ Boer × ½ nondescript breed goats, Canindé, and Moxotó) on carcass quantitative characteristics and non-carcass components (NCC) were evaluated. Forty-five intact male goats were distributed in a 3 × 3 factorial design with five replicates. There was no effect of genotype on carcass weights and yields and retail cuts weights and yields (P > 0.05). Compared to Moxotó, ½ Boer presented better carcass conformation and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
4
1
1
Order By: Relevance
“…The NRC (2007) recommends metabolizable protein requirements for growth 39% greater for meat goats than dairy and indigenous type, which may be due to differences in NP g and/or in k pg , as previously mentioned. One may think that in each kilogram gained, meat-type goats have more protein than indigenous or dairy goats (Warmington and Kirton, 1990;Gibb et al, 1993;Cameron et al, 2001;Martins et al, 2014); however, we did not observe such pattern in the present work. The goat database used to derive recommendations by the AFRC (1998) encompasses mainly data from castrated dairy goats, which may explain the lower protein requirements for gain.…”
Section: Energy and Protein Requirements In Goatscontrasting
confidence: 83%
“…The NRC (2007) recommends metabolizable protein requirements for growth 39% greater for meat goats than dairy and indigenous type, which may be due to differences in NP g and/or in k pg , as previously mentioned. One may think that in each kilogram gained, meat-type goats have more protein than indigenous or dairy goats (Warmington and Kirton, 1990;Gibb et al, 1993;Cameron et al, 2001;Martins et al, 2014); however, we did not observe such pattern in the present work. The goat database used to derive recommendations by the AFRC (1998) encompasses mainly data from castrated dairy goats, which may explain the lower protein requirements for gain.…”
Section: Energy and Protein Requirements In Goatscontrasting
confidence: 83%
“…Animals with a greater slaughter weight tended to exhibit greater values for carcass measurements (Table 1). MARTINS et al (2014) observed that in Boer, Canindé and Moxotó kids fed ad libitum, there was an increase of the carcass internal length, chest depth and rump circumference in comparison with kids subjected to 25% and 50% feed restriction. DHANDA et al (2003) also reported an increase of carcass length according to the increase in the weight at slaughter in distinct breeds (Boer, Angorá, Feral and Saanen), slaughtered at intervals of 14-22kg and 30-35kg.…”
Section: Resultsmentioning
confidence: 90%
“…Os cordeiros F 1 SI x RL apresentaram maiores pesos de sangue, trato gastrointestinal cheio, conteúdo gastrintestinal e pulmão+traquéia em relação ao RL. Contudo, não houve influência no rendimento de carcaça, mas é necessário considerar além do porte, a maturidade dos animais (Martins, 2014) …”
Section: Resultsunclassified